Phellinus piptadeniae (Hymenochaetales: Hymenochaetaceae): taxonomy and host range of a species with disjunct distribution in South American seasonally dry forests - Salvador Montoya, Carlos Alberto (2015)
Phellinus piptadeniae (Hymenochaetaceae, Hymenochaetales) is traditionally characterized by having applanate to ungulate basidiome with the pilear surface concentrically sulcate, radially cracked in old specimens, and a notorious sinuous black line in the cross section of the context. The species has been recorded in different Brazilian biomes, often associated with legume hosts and seasonally dry vegetation. It occurs highly specifically associated with Piptadenia gonoacantha in semideciduous forest of the Atlantic Forest domain at the type locality in São Paulo state, southeastern Brazil. In the Caatinga dry woodlands, northeastern Brazil, Phellinus piptadeniae occurs as host-recurrent of different Piptadenia species. During a recent polypore survey in different remnants of southeastern Atlantic Forest, specimens with the same morphology of the type were collected and the same host (P. gonoacantha) was confirmed. Morphologically similar specimens newly collected in seasonally dry tropical forests of northwestern Peru were also recorded on legume hosts (Libidibia glabrata and Pithecellobium excelsum). In this paper we discuss the morphological variation, host range, and distribution of Phellinus piptadeniae in the context of the historical biogeography of the neotropical Seasonally Dry Tropical Forest (SDTF) biome. Some putative taxonomic implications that should be further investigated in a molecular phylogenetic framework are also addressed.